THE INFLUENTIAL FACTORS ON THE PATIENTS SATISFACTION AND INTENT TO BEHAVE: A CASE STUDY IN NORTH SULAWESI PROVINCE - Silvya Lefina Mandey (Journal of Economics, Business, and Accountancy Ventura, 2013)
The research analyses the effect of service quality on the hospital’s patients satisfaction and patientsintent to behave, the effect of intent to behave, medical team behavior on patients satisfaction andpatients intent to behave, the effect of communication quality on patients satisfaction and patient intentto behave, patient’s trust on the intent to behave, and patient satisfaction on the intent to behave.The sample consists of whole patients who had been undergoing normal treatment at the hospital attheir own health insurance service or ASKES, in the North Sulawesi province. The data were collectedusing non-probability sampling that was an accidental sampling technique. The sample was of300 respondents. The analysis was done using the SEM (Structural Equation Modeling) with AMOS(Analysis of Moment Structural) software as supporting program. It can be concluded that servicequality has a significant effect on the patient’s satisfaction. Service quality, organizational citizenshipor medical team at the hospital behavior, and trust all have a significant effect on the patients’ intentto behave that is they remain loyal. Trust has also a significant effect on the patient intent to behave.However, the patients’ satisfaction has no significant effect on their intent to behave.